2019
DOI: 10.1080/20786190.2019.1613061
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of community health workers on their training, teamwork and practice: a cross-sectional study in Tshwane district, Gauteng, South Africa.

Abstract: In 2011, South Africa established ward-based outreach teams (WBOTs) comprising Community Health Workers as part of strategies to strengthen primary healthcare. The new community health workers (CHWs) lacked experience of the programme. This study aimed at assessing perceptions of community health workers on their training, teamwork and practice. Methods: This was a cross-sectional study conducted among CHWs in the seven regions of Tshwane health district between October and November 2015. Data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…However, due to contextual challenges, the delivery of the intervention is, in practice, not feasible via CHWs linked to a PHC facility. This is in line with other studies examining CHW systems in South Africa and other LMIC settings [ 20 , 35 37 ], as CHWs have become a cadre of health workers to whom various new tasks are assigned, without necessarily much consultation or consideration of their capacity in terms of time, working conditions or skills.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, due to contextual challenges, the delivery of the intervention is, in practice, not feasible via CHWs linked to a PHC facility. This is in line with other studies examining CHW systems in South Africa and other LMIC settings [ 20 , 35 37 ], as CHWs have become a cadre of health workers to whom various new tasks are assigned, without necessarily much consultation or consideration of their capacity in terms of time, working conditions or skills.…”
Section: Discussionsupporting
confidence: 88%
“…This route through community-based organisations is not without its own challenges, such as higher costs and possibly limited potential for scalability and sustainability compared to that of the public sector. Implementation of CHW programmes through community-based organisations has also been criticised for lacking accountability [ 20 ], and it ignores the need to the strengthen community health systems through the public sector [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 A recent study determined that social conditions do have an impact on the mental health of an individual. 36 Although there is evidence that CHWs are not always safe when they enter the homes of patients with mental health problems, 37 concern for safety was not raised in this study. Rather, CHWs observed the need to understand the patient and how to communicate depending on the mental health status of the patient, and CHWs in this study demonstrated empathy towards their clients’ mental health needs.…”
Section: Discussionmentioning
confidence: 73%
“…Although limited, available evidence of CHW experiences from rural South Africa largely mirrors the global literature. CHWs in South Africa identify training (Nyalunga et al, 2019), supervision (Assegaai & Schneider, 2019), remuneration, and logistical factors (Austin-Evelyn et al, 2017) as issues shaping their work lives.…”
mentioning
confidence: 99%